Integrating Digital Technology and Project-Based Learning in Secondary School Chemistry: Innovative Strategies for Conceptual Understanding - Masbukhin, Faizal Akhmad Adi; Kusmawan, Udan (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The advancement of digital technology and the growing demand for student-centered learning have prompted educators to explore more innovative approaches in science education. In chemistry, abstract concepts often pose significant challenges for learners, particularly at the secondary school level. This study aimed to examine how practising chemistry teachers integrate digital technology and project-based learning (PjBL) to enhance students’ conceptual understanding. A descriptive qualitative design was employed, involving in-depth interviews with 22 secondary school teachers who are also distance education students. Thematic analysis revealed that combining video-based instruction, interactive simulations, and contextualized PjBL strategies significantly improved students’ comprehension of complex topics such as atomic structure, chemical bonding, and colligative properties. For example, digital simulations enabled clearer visualization of atomic models, while hands-on projects like “Ice Cream Making to Explore Colligative Properties” successfully connected theoretical knowledge with real-life experiences. Despite the pedagogical advantages, challenges such as disparities in digital literacy and the limitations of online platforms were noted. This study contributes to the evolving field of chemistry education by offering practical insights into the implementation of digital and project-based strategies tailored to the learning preferences of Generation Z and Alpha students. The findings underscore the need for systemic teacher support, professional development, and infrastructure improvement to maximize the benefits of these transformative teaching approaches.